(untitled) (Proceedings of the International Conference on Future of Education, 2019)
The significance of critical thinking as one of the 21st century skills makes the Indonesian Ministry of Education and Culture integrate Higher Order Thinking Skill (HOTS) in the latest national curriculum. It requires teachers, as the curriculum implementers, facilitate students to be critical thinkers through the teaching and learning process. Besides, the teachers need to have competence in developing HOTS – based questions in order to assess the students’ HOTS. However, teachers’ ability in this field is still disappointing. The aim of this study was to investigate the challenges faced by Indonesia English as Foreign Language (EFL) teachers in developing HOTS – based questions. The study employed qualitative method and made use of questionnaire to collect the data. The research participants were EFL teachers of secondary school level in some different regions in Indonesia. The findings showed that, despite the importance of HOTS, some factors were claimed as challenges for the teachers in developing HOTS – based questions, among others was the teachers’ varied-perceptions towards HOTS. The challenges were classified into three aspects, namely teachers’ aspect, teaching and learning aspects, and students’ aspect. Hence, the conclusion was drawn to improve educational practice and as insights for educational stakeholders and policy makers.